Medieval Soldier database (2009)
Our database contains the names of soldiers serving the English crown from the late 1350s to 1453. Most were fighting the French. In this second phase of the Hundred Years War major invasions of France were launched, including that of 1415 which culminated in Henry V’s victory at Agincourt 1415. We have also included soldiers serving in other theatres (Scotland, Ireland, Wales, Spain, Calais etc), and in all types of service (expeditions on land and sea, garrisons, escorts, standing forces). Why do we know so many names? The simple explanation is that soldiers received pay and this had to be audited. The financial officials of the crown were keen to check the soldiers were present and correct. The main way of doing this was by checking off their names at a muster, at the beginning of a campaign or during it, or every few months for troops in garrison. Thousands of muster rolls survive in archive collections in England, France and beyond. We also have the evidence of letters of protection which soldiers bought from the Chancery to prevent legal actions whilst they were absent from home.
Keywords: _open access

Medieval Libraries of Great Britain
Keywords: _open access

Digital Bodleian
Keywords: _open access

Famine and Dearth database

Putting UK collections on the map - Rees, Arran (Museum Data Service, 2025)
We've been working working hard to beef up our interactive guide to the UK's museum collections. Here's what's new.

Churchill Archive Platform - Churchill Acquired Papers New Collection
In 2024,the Acquired Papers were included in the Churchill Archive,spanning items such as previously unseen personal letters,speech notes and diary en
Keywords: _no subscription

The Royal Mint Museum
The Royal Mint Museum contains a valuable numismatic library of some 15,000 volumes. This includes archival material acquired in large part from departments of the old Royal Mint at Tower Hill, such as the Engraving Department, the Die Office and the Pyx Office. For the most part this material dates back to the beginning of the 20th century and in its day-by-day character is a useful adjunct to the official files in The National Archives and to the published Annual Reports of the Royal Mint.

The Material Culture of Wills: England 1540-1790 | Zooniverse - People-powered research
Help us transcribe wills from the sixteenth to eighteenth centuries, and reveal how ownership of, and attitudes towards, objects changed in a period of economic transformation

The Royal College of Surgeons of Edinburgh

BFI National Archive (BFI)
The BFI looks after one of the largest and most important collections of film and television in the world. Its teams of experts ensure that the collection is preserved and developed for future generations and made widely accessible to today’s audiences.
Keywords: _open access

The National Farm Survey, 1941–1943: Collection highlights (The National Archives)
The National Farm Survey was created during the Second World War to increase food production and to plan for post-war agriculture.

Dataset Card for British Library Books
We’re on a journey to advance and democratize artificial intelligence through open source and open science.
Keywords: _open access

Historic UK Newspaper Datasets (2024)
This dataset contains text extracted at the article level from historic digitised newspapers from the Heritage Made Digital newspaper digitisation program at the British Library. The newspapers in the dataset were published between 1800 and 1896. This dataset contains ~2.5 billion tokens and 3,065,408 articles. The dataset contains text generated from Optical Character Recognition software on digitised newspaper pages. This dataset includes the plain text from the OCR alongside some minimal metadata associated with the newspaper from which the text is derived and OCR confidence score information generated from the OCR software.
Keywords: _open access

Unlocking the Records of London’s Medieval Foreign Trade - vanessarockel (On History, 2024)
This blog post was written by Dr Stephen Gadd, Software Developer and GIS Consultant. The IHR’s Centre for the History of People, Place and Community has been carrying out some exploratory research on the potential of analysing London’s medieval customs accounts digitally. Detailed, or ‘particular’ customs accounts recorded immense detail about the goods and practices […]

Old Bailey Online - The Proceedings of the Old Bailey, 1674-1913 - Central Criminal Court
Keywords: _open access

Runaway Slaves in Britain

Legacies of British Slavery

British History Online
The core printed primary and secondary sources for the medieval and modern history of the British Isles
Keywords: _open access

British Library Sounds (The British Library)
Oral history. Interviews covering a wide range of subject areas related to British life and culture, including art, architecture, economics, social welfare, disability, music, sports, theatre, politics, photography, and more.
Keywords: _open access

Early English Books Online
EEBO - Base contenant les œuvres recensées des Short Titles Catalogues 1 et 2 (basés sur les catalogues Pollard & Redgrave et Wing), soit quelque 125 000 documents publiés en anglais entre 1475 et 1700, dans tous les domaines de la connaissance
Keywords: _NO SOFIA; _UdeM only

Eighteenth century journals, 1685-1835 - Adam Matthew Publications
Périodiques anciens publiés en Angleterre (entre 1685 et 1835), témoins des aspects sociaux, politiques et littéraires du 18e siècle.
Keywords: _UdeM only

Public petitions to Parliament, 1833-1918 - Great Britain. Parliament
Contient des pétitions de la population britannique sur des questions politiques, ecclésiastiques, criminelles, coloniales, culturelles, sociales fiscales, sur l'éducation , etc. Permet aux chercheurs d'exploiter de nouvelles sources sur le rôle formateur des pétitions au Parlement au cours du dix-neuvième siècle (1833-1918), une période de modernisation politique et de démocratisation en Grande-Bretagne.
Keywords: _UdeM only

Mass Observation Online, 1937-1972 - Adam Matthew Publications
British Social History. Donne accès à près de 115 000 images numériques des archives du projet Mass Observation: manuscrits et documents dactylographiés, publications imprimées, essais, photographies, rapports d'enquête et d'observation, relevés sociographiques, etc. Projet mis sur pied pour étudier l'histoire sociologique de la population de Grande-Bretagne à partir de 1937 et qui s'étend tout au long des décennies 1940, 1950 et 1960.
Keywords: _UdeM only

Eighteenth Century Collections Online - Thomson Gale
ECCO donne accès aux images numérisées de chaque page de 150 000 livres publiés durant le dix-huitième siècle, principalement en Grande-Bretagne, mais aussi ailleurs en Europe et en Amérique. Cette base regroupe des collections d'ouvrages importants et rarement disponibles en format électronique, dont les oeuvres complètes de 28 auteurs marquants. Elle permet la recherche en texte intégral d'environ 26 millions de pages de divers types de documents touchant à de nombreux domaines dont l'histoire, la géographie, la littérature, la philosophie, la religion, le droit, l'art et la science.
Keywords: _UdeM only

Defining gender, 1450-1910 - Adam Matthew Publications
Manuscrits, publications, pamphlets, correspondances, manuels d'éducation à la bienséance et ouvrages concernant la sexualité et le genre produits en Grande-Bretagne avant 1910.
Keywords: _UdeM only

British Pathé
Keywords: _open access

Empire Online - Adam Matthew Publications
Sources manuscrites et imprimées témoignant du développement de l'empire britannique
Keywords: _UdeM only

The Proceedings of the Old Bailey, 1674-1913 - Central Criminal Court
Keywords: _open access

The National Archives, UK
Official archive of the UK government, and for England and Wales.. Spanning 1000 years of history. Non-ministerial department.
Keywords: _open access

Data Foundry
Keywords: _open access

National Records of Scotland - Team, National Records of Scotland Web (National Records of Scotland)
Keywords: _open access

Digital collections (The British Library)
Keywords: _open access